Perceived psychosocial safety climate (PSC) level and its association with occupational outcomes among clinical unit healthcare workers in a Malaysian hospital: a three-wave longitudinal study - Abu Bakar, Norhasliza; Bulgiba, Awang; Isahak, Marzuki (BioMed Central Ltd, 2025)
Introduction: The Psychosocial Safety Climate (PSC) is a potent organizational construct. It concerns senior management values and attitudes toward care and practices in relation to employees’ psychosocial well-being and psychological outcomes. Objective: This study aimed to determine the PSC level, its distribution and associated factors as perceived by healthcare workers in clinical units of a tertiary level hospital in Malaysia. Methods: A three-wave longitudinal study over one year was conducted using a self-administered questionnaire among healthcare workers in the University of Malaya Medical Centre (UMMC), Malaysia. Data were collected at baseline (Time 1, T1), three-month interval (Time 2, T2) and nine-month interval (Time 3, T3) from 618 participants who remained enrolled throughout. The validated Malay version of the PSC-12 Scale questionnaire was used to measure psychosocial safety climate level. Results: We found the PSC score to have a median of 42.88. There was a good psychosocial work environment (mean PSC score 41.44 ±8.27). The majority (61.1%) of study participants perceived a high PSC score (≥ 41) which is concordant with a good psychosocial work environment. Low PSC score (≤ 37) was perceived by 28.5% and 9.0% perceived a moderate PSC score (38–40). PSC scores improved significantly from T1 to T3 (mean difference = 1.417, 95% CI 3.037, 5.456). A higher PSC score was reported among Malay healthcare workers compared to the non-Malay group (mean difference = 3.16, 95% CI 0.007, 6.315). Nurses and paramedics had lower PSC scores than support staff (mean difference = -2.50, 95% CI -4.310, -0.069). Despite a good perceived PSC level, our study did not reveal significant association between PSC level with sickness-leave (B = − 0.03, p = 0.624, 95% CI − 0.144, 0.087) and job performance (B = − 0.02, p = 0.443, 95% CI -0.090, 0.040), even after adjusting for other socio-demographic and occupational covariates. Conclusion: Perceived PSC was high among participating healthcare workers with a progressively better PSC score at each timepoint over the one-year study. The support group of healthcare workers perceived better PSC scores possibly due to lesser responsibility compared to nurses and paramedics. An improved study design with additional variables to measure the job performance and work engagement is essential to provide vigorous evidence in future research.